A macrobending singlemode fiber refractive index sensor for low refractive index liquids - Wang, Pengfei; Semenova, Yuliya; Li, Yong; Wu, Qiang; Farrell, Gerald (Photonics Letters of Poland, 2010)
An all-fiber refractive index sensor with a simple configuration is proposed and investigated. The proposed fiber refractometer consists of a full-loop structure of bare high-bend loss singlemode fiber-1060XP, employing the well-known whispering gallery mode (WGM) effect induced by the evanescent wave excitation to measure the refractive index of an external medium. A competitive sensitivity is achieved (average 725.76nm/RIU at a bend diameter of 19.3mm) compared with other fiber-optic sensors, plus benefits resulting from simplicity, low cost and ease of fabrication. Full Text: PDF References: I. Del Villar, I. R. Matias, and F. J. Arregui,"Enhancement of sensitivity in long-period fiber gratings with deposition of low-refractive-index materials", Opt. Lett. 30, 2363 (2005).[CrossRef] W. Liang, et al,"Highly sensitive fiber Bragg grating refractive index sensors", Appl. Phys. Lett. 86, 151122 (2005).[CrossRef] B. Gauvreau, et al,"Photonic bandgap fiber-based Surface Plasmon Resonance sensors", Opt. Express 15, 11413 (2007).[CrossRef] T. Wei, et al,"Temperature-insensitive miniaturized fiber inline Fabry-Perot interferometer for highly sensitive refractive index measurement", Opt. Express 16, 5764 (2008).[CrossRef] P. Wang, et al,"Macrobending single-mode fiber-based refractometer", Applied Optics 48, 6044 (2009).[CrossRef] J.Zhang, D.Grischowsky,"Whispering-gallery-mode cavity for terahertz pulses", JOSA B 20(9), 1894 (2003).[CrossRef] S. H. Nam and S. Yin,"High-temperature sensing using whispering gallery mode resonance in bent optical fibers", IEEE Photon. Technol. Lett. 17, 2391 (2005).[CrossRef] W. P. Huang, C. L. Xu,"Simulation of three-dimensional optical waveguides by a full-vector beam propagation method", IEEE J. Quantum Electron. 29, 2639 (1993).[CrossRef] P. Wang, et al,"Accurate theoretical prediction for single-mode fiber macrobending loss and bending induced polarization dependent loss", Proceeding of SPIE 7003, 7003-1Y (2008).[CrossRef]